SYNTHESIZING SOCIAL MEDIA INTO THE FABRIC OF RELIGIOUS EDUCATION: EXPLORING ADVANTAGES, CONFRONTING COMPLEXITIES, AND UNRAVELLING FAR-REACHING IMPLICATIONS - Nana Suryapermana; Loso Judijanto; Yahdinil Firda Nadirah; Dede Gustian; Moch. Subekhan (Adisam Publisher, 2024)
This study delves into integrating social media into religious education, examining its advantages, complexities, and far-reaching implications.We used a mixed-methods research design to survey and interviewed educators, students, and administrators across diverse religious education settings. Quantitative analysis revealed that 70% of participants acknowledged heightened student engagement through social media, while 62% recognized its positive impact on learning outcomes. However, 45% expressed concerns about ethical considerations, and 55% found the integration challenging. Qualitative insights unveiled a rich tapestry of community building and collaborative learning juxtaposed with challenges related to online etiquette and the digital divide. The study contributes to the field by validating the positive outcomes of social media integration in religious education while emphasizing unique ethical considerations. Limitations include the potential for response bias and a focus on a specific timeframe. Recommendations for future research include longitudinal studies and comparative analyses across religious traditions. In conclusion, this research illuminates the complex interplay of technology, ethics, and tradition in religious education, offering insights for educators, policymakers, and researchers navigating this dynamic landscape.